2020
DOI: 10.1007/s12298-020-00910-2
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of maize ZmPP2C26 gene promoter in drought-response

Abstract: The clade A members of serine/threonine protein phosphatase 2Cs (PP2Cs) play crucial roles in plant growth, development, and stress response via the ABA signaling pathway. But little is known about other PP2C clades in plants. Our previous study showed that maize the ZmPP2C26, a clade B member of ZmPP2Cs, negatively regulated drought tolerance in transgenic Arabidopsis. However, the upstream regulatory mechanism of ZmPP2C26 remains unclear. In the present study, the expression of ZmPP2C26 gene in maize was ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The PP2C gene family is one of the largest families of plant and has been identified as important members playing crucial roles in phytohormone signaling, developmental processes, biotic and abiotic stress responses [8,17,36], however, PP2C genes from walnut trees was still not reported. In order to reveal the adversity adaptation mechanism of walnuts then to provide a basis for walnut cultivation and management to ensure the yield and quality, in this study, 41 walnut PP2C genes those may have potential functions in stress response were identified (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PP2C gene family is one of the largest families of plant and has been identified as important members playing crucial roles in phytohormone signaling, developmental processes, biotic and abiotic stress responses [8,17,36], however, PP2C genes from walnut trees was still not reported. In order to reveal the adversity adaptation mechanism of walnuts then to provide a basis for walnut cultivation and management to ensure the yield and quality, in this study, 41 walnut PP2C genes those may have potential functions in stress response were identified (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…PeHAB1 could interact with the ABA receptor PYL4 in an ABA-independent manner to reduce tolerance to drought in poplar [16]. In maize, ZmPP2C26 has a negative regulatory effect against drought stress [17]. Tomato SlPP2C gene family that encoding the core component of ABA signaling could regulate tomato fruit development and be induced by drought [18].…”
Section: Introductionmentioning
confidence: 99%
“…ZmPP2C26 negatively regulates drought tolerance by dephosphorylating mitogenactivated protein kinases (ZmMAPK3 and ZmMAPK7). Yeast two-hybrid screening showed that ZmPP2C26 interacts with ZmMAPK but not ZmPYLs, confirming the role of ZmPP2C26 in MAPK signaling (Lu et al, 2020(Lu et al, , 2022. However, the roles of ZmMAPK3 and ZmMAPK7 in the response of maize to drought stress require further study.…”
Section: Genes That Function In Drought Resistance During the Seedlin...mentioning
confidence: 80%
“…In this study, most TrIAA gene promoters contained growth hormone-responsive (AuxRE/TGA-element) cis-elements or their variants [ 50 ]. Some TrIAA gene promoters have been reported to contain cis-elements involved in abiotic stress response, for example, LTR is involved in low temperature response [ 51 ], MBS plays a role in drought- inducibility [ 52 , 53 ], ARE is involved in anaerobic induction, and TC_rich_repeats are involved in defense and stress response [ 54 ]. In conclusion, the different types of cis-elements on the promoters of the TrIAA gene family reflect the complexity and diversity of gene expression regulation and evolution.…”
Section: Disscussionmentioning
confidence: 99%